Implementasi Media Padlet dalam Pembelajaran Teks Artikel di Kelas 12 SMA Negeri 9 Semarang - Fahrudin Bustomi; Brillian Syaifullah; Khusnul Fadlyanim; Asep Purwo Yudi Utomo; Arka Yanitama; Eva Wulandari; Samsiati Samsiati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Changing curricula and the rapid development of technology make educators and students have to be able to technology as a medium in learning. The use of technology in education needs to be done to increase student activity so that student learning outcomes increase. The purpose of this research is to increase student acticity, critical thingking, creativity, collaboration, so that learning using the media padlet can run smoothly and optimally. The method used in this study is descriptive qualitative through data triangulation, namely observation, documentation, and questionnaire distribution. The results of this study, namely grade 12 students at SMA Negeri 9 Semarang can increase their learning activity throught the padlet media and increase student learning outcomes.